Stavropol medical institute to help the front - I. V. Kartashev (Гуманитарные и юридические исследования)
Introduction. An important role in achieving the victory of the Soviet people over Nazi Germany in the Great Patriotic War was played by training institutions that the Red Army badly needed - military, engineering, medical. One of the higher educational institutions that trained doctors for the front and rear in the south of the country was the Stavropol State Medical Institute. However, information about his activities in a number of areas during this period of time was largely fragmentary.Materials and methods. The study is based on the analysis of documents and materials from the funds of the Central Archive of the Ministry of Defense of the Russian Federation and the State Archive of the Stavropol Territory, the archive and museum of the Stavropol State Medical University, the analysis of regional printed publications during the Great Patriotic War, as well as the results of previous scientific works on this issue. Based on a combination of information from various sources, the activities of the medical institute and its employees in providing assistance to the front both before the occupation of Stavropol and after its liberation from German troops are comprehensively considered.Analysis. The analysis showed that, along with the main task of training highly qualified medical workers by the university, its employees actively provided other assistance to the front.Results. In the course of the study, it was found that the specialists of the clinical departments of the university took an active part in the work of the evacuation hospitals of the city and the region, on the territory of which the largest hospital base of the Soviet troops was deployed. Research staff of the institute, among whom there were a large number of prominent scientists, participated in the development of military medical topics. Employees and students of the university were engaged in social, educational and propaganda activities, provided financial assistance to the front.